Influences of Organizational Culture in the Adoption of Agile Methodologies in Information Systems Development A Systematic Mapping - Junior, Gerson; Amaral, João; Matsubara, Patrícia; Neto, Valdemar (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2015: Anais do XI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2015.5821, 2015)
Information Systems (IS) industry has been pressured to deliver software products under reduced time-to-market and restrict budget. Agile Methodologies (AM) have been adopted to meet those aforementioned needs by the adoption of self-managing teams, iterative development cycles, fast delivery, and focus on functional software. Adoption of AM requires a suitable organizational environment, with significant changes in the employees’ behavior and in the working processes, impacting, and suffering the impact of Organizational Culture (OC). In this direction, methods, actions, and policies must be thought to align the company’s OC to the use of AM, in such a way that both can benefit each other. However, there is a lack of proposals that systematically investigate how to align both OC and AM. In this sense, a systematic mapping study (SMS) was conducted to identify studies that associate OC in initiatives of AM adoption. This paper presents the state-of-the-art about the influence of OC in the adoption of AM. The main contribution of this paper is bringing up an overview of the area, indicating perspectives of research, and exposing (i) a list of actions which have been reported to align OC and AM; (ii) OC factors recognized as essential to the successful adoption of AM; and (iii) the perceptions on a lack of awareness about the influence of OC in IT organizations.